Evaluation of Water Pollution Due to Tofu Industrial Waste: Studies Case and Strategy Countermeasures - Hanifta Man Andira, Muhammad; Fajri, Roifah; Enova Rahmadhani, Sakina; Hasna Rosyida, Sharifah; Hawali Abdul Matin, Hashfi (Diponegoro University, 2024)
Tofu waste is the remaining or unused waste material from the tofu making process. Krajan Village is one of the areas where tofu industry can easily be found around it. The community who are tofu industry players usually dump their waste into the river. Liquid and solid waste from the tofu industry can reduce environmental quality and affect living things if not managed properly before being discharged into the drain. In addition, polluted river water can contain hazardous substances that have a negative impact on flora and fauna and increase the risk of disease for people whose lives depend on river water for their daily needs. Therefore, this waste must be treated first to meet the appropriate water quality standards before being discharged into the airway. The purpose of this study was to determine the level of air pollution produced by the tofu industry in the river, identify the main sources of pollution in the Krajan River, and develop appropriate and appropriate mitigation strategies to overcome pollution problems on its way to its destination. The results of the study showed that the TDS, temperature, and pH parameters that had been tested in the Krajan River were below the reference quality standard limits, namely the Central Java Provincial Regulation Number 5 of 2012 concerning Wastewater Quality Standards. However, residents around the river still feel the impacts, such as the unpleasant odor that is often smelled in the air and dust from tofu industry activities that disrupt daily activities due to river pollution from tofu industry waste, household waste, and livestock waste that is dumped directly without prior processing.